Hydrogenation of a TiFe-based alloy at high pressures and temperatures. (2nd March 2015) - Endo, Naruki; Saita, Itoko; Nakamura, Yumiko; Saitoh, Hiroyuki; Machida, Akihiko
Abstract We investigated the hydrogenation of a ternary TiFe0.8Mn0.2 alloy under high pressure (up to 6.5 GPa) and at high temperature (up to 600 °C) by in situ synchrotron radiation X-ray diffraction measurements. A chemical order–disorder phase transition and the formation of body-centered cubic (BCC) hydride were observed. The phase-transition temperature was 400 °C, which is 200 °C lower than that of a binary TiFe alloy. A disproportionation reaction, which was observed for the binary TiFe alloy, did not occur at this temperature. The BCC hydride existed stably, and new hydrides were not formed after the BCC hydride became a single phase. Since the unit cell volume of the BCC hydride was almost equal to that of the γ hydride, TiFe0.8Mn0.2H1.8, under the same pressure–temperature conditions, the hydrogen content of the former was roughly estimated as the same as that of the latter (hydrogen to metal atom ratio = 0.9).